Yape, quality and satisfaction according to the service - Machaca Vargas, Yeni Leticia (2024)
Taking into account that globalization generates greater economic dynamism, banks must opt for new ways to keep their products in the market. Therefore, the main purpose of this research is to describe the quality and satisfaction that the Yape digital application provides to the user and to know the relationship that exists between quality and satisfaction. The students of the fifth, seventh and ninth semester of the Professional School of Administration of the National University of San Agustín de Arequipa were considered as users. Students between 18 and 23 years of age were taken as a sample. IBM SPSS software was used in the Spearman method and Cronbach's alpha to determine data validation and reliability. The work was carried out under a descriptive method with a quantitative approach and correlational scope. The results show that quality and service are in a close and direct relationship. Because both complement each other. Furthermore, 98.7 % of the population sample agree or totally agree that the Yape digital application is easy to use, and its software design meets the needs presented. It is concluded that the hypothesis about the high satisfaction of university students of the Faculty of Administration towards the services provided by Yape is valid. It is worth mentioning that technology continues to develop, and it is essential to be flexible to change.